2020
DOI: 10.3390/biomedicines8060163
|View full text |Cite
|
Sign up to set email alerts
|

Air Contamination in Different Departments of a Tertiary Hospital. Assessment of Microbial Load and of Antimicrobial Susceptibility

Abstract: Air contamination in the hospital setting can be a reason for the spread of nosocomial infection among susceptible patients. The aim of this study was to identify bacterial species, and their load and drug resistance, in the air of a tertiary hospital. Air samples were collected on a monthly basis for 12 consecutive months in four different departments of the hospital (Intensive Care Unit (ICU), Internal Medicine Ward (IMW), Surgical Ward (SW), and Neonatal Unit (NU)). In total, 101 samples were collected, out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In fact, the airborne Gram-positive cocci (Staphylococcus and Micrococcus) were also the most detected bacterial genera in a sensitive ward of an academic pediatric hospital in Iran [84], in hospitals in India [85], in a hospital ward in India [67], in five educational Hospital wards air in Iran [86], in General Hospitals of Korea [87], in a regional Danish hospital [88] and in tertiary university hospital in NE Greece [89]. In our study, higher gram-positive cocci isolates were found in the treatment rooms and vaccination rooms of both PHCC, smaller spaces where they perform nursing treatments, shared between workers and patients, exposing them to both.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the airborne Gram-positive cocci (Staphylococcus and Micrococcus) were also the most detected bacterial genera in a sensitive ward of an academic pediatric hospital in Iran [84], in hospitals in India [85], in a hospital ward in India [67], in five educational Hospital wards air in Iran [86], in General Hospitals of Korea [87], in a regional Danish hospital [88] and in tertiary university hospital in NE Greece [89]. In our study, higher gram-positive cocci isolates were found in the treatment rooms and vaccination rooms of both PHCC, smaller spaces where they perform nursing treatments, shared between workers and patients, exposing them to both.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive drug resistance was defined as non-susceptibility to at least one agent in all but two or fewer antimicrobial categories. 7 …”
Section: Methodsmentioning
confidence: 99%
“…The results of the calculation of S. aureus bacterial colonies with colony counters were analyzed descriptively and tabulated. Calculation of the number of S. aureus bacteria follows the following equation (Tselebonis et al, 2020).…”
Section: Total Bacteria Count =mentioning
confidence: 99%